Towards the Story of the Parishes’ Reunion of the West European Exarchate with the Moscow Patriarchy in Post-War Years (1945–1946) - Kostriukov Andrei (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article covers the circumstances of the consolidation of parishes of Russian tradition in the West European exarchate with the Moscow Patriarchy in 1945. The author has analyzed the subsequent circumstances that assisted the parties with the rupture of relations in 1946. On the basis of the documents the author has drawn the conclusion about the primary fragility of the ﬁrst consolidation that was hasty made, nonmetering speciﬁc jurisdictional features of the West European exarchate. Serious problems on the way to unity have arisen in August, 1945, when the representative of the Moscow Patriarchy, metropolitan Nicolay (Jarushevich), had arrived to Paris. Objections against the consolidation have run as follows: the Church in the USSR continued to be in enslavement by the atheistic government. Despite the arguments of association’s opponents, metropolitan Evlogy has agreed to be the part of the Moscow Patriarchy. The next months the positions of the opponents have become stronger because of metropolitan Evlogy who remained the exarch of both Ecumenical and Moscow Patriarchs. In February, 1946 at the ceremony of ordination, bishop Nikon (Greve) has sworn not to Moscow, but to the Constantinople patriarch. The decree of the Presidium of the Supreme council of the USSR from June, 14th, 1945 about citizenship that was granted to Russian emigrants in France became the serious strike on the unity. In the Exarchate the delimitation between those who has accepted the Soviet citizenship and those who has refused has begun. Thus the diocesan council, being afraid of freedom’s infringement, prepared a soil for the future separation from the Moscow Patriarchy. In July, 1946 the diocesan council made the memorandum that the policy of the further rapprochement with the USSR and the Moscow Patriarchy threatened the Exarchate with split. After metropolitan Evlogy’s death the division became the accomplished fact.